Gambaran Pola Asuh pada Baduta dalam Pencegahan Stunting - Mamat Lukman; Titin Sutini; Hilmi Adillah (Jurnal Keperawatan Silampari, 2023)
This study aims to provide an overview of the parenting style given to toddlers to prevent stunting. This research method uses narrative review by searching articles using electronic databases, namely EbscoHost, ResearchGate, and CambrigdeCore. The results of this study in the literature review found that the four types of parenting (authoritative, authoritarian, permissive, not involved) have a close relationship with the incidence of stunting. Three parenting styles have an impact that prevents stunting, but two of them are accompanied by adverse effects that support stunting. In contrast, the other parenting style is a parenting style that altogether causes stunting. In conclusion, the parenting style best applied to toddlers in the context of stunting prevention is mixed. Still, authoritative parenting is the most recommended parenting style compared to the other three parenting types. Keywords: Baduta, Prevention, Parenting, Stunting